1993
DOI: 10.1159/000227193
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hepatocellular Carcinomas in the Egyptian Toad <i>Bufo regularis</i> by an Antifungal Drug (Griseofulvin)

Abstract: Neoplastic lesions (hepatocellular carcinomas) were induced in the liver in 18 of 100 experimental toads (Bufo regularis) force fed with the antifungal drug griseofulvin, at a dose level of 0.4 mg/50 g every day. Maximal time of exposure and observation was 12 weeks. The first tumors appeared in 2 male toads 4 weeks after the initiation of feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The models have in cluded Xenopus laevis [4][5][6], Rana pipiens [7,8] and Bufo regularis [9,10], Some investigators have shown that toads can be used as a model to study the development of carcinogens [11], cocarcinogens [12] and vitamins [13], In the majority of these studies, the diagnosis of the induced tumors was based essentially on light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The models have in cluded Xenopus laevis [4][5][6], Rana pipiens [7,8] and Bufo regularis [9,10], Some investigators have shown that toads can be used as a model to study the development of carcinogens [11], cocarcinogens [12] and vitamins [13], In the majority of these studies, the diagnosis of the induced tumors was based essentially on light microscopy.…”
Section: Introductionmentioning
confidence: 99%